2010
DOI: 10.1186/1475-2875-9-59
|View full text |Cite
|
Sign up to set email alerts
|

High heterogeneity in Plasmodium falciparum risk illustrates the need for detailed mapping to guide resource allocation: a new malaria risk map of the Lao People's Democratic Republic

Abstract: BackgroundAccurate information on the geographical distribution of malaria is important for efficient resource allocation. The Lao People's Democratic Republic has experienced a major decline in malaria morbidity and mortality in the past decade. However, efforts to respond effectively to these changes have been impeded by lack of detailed data on malaria distribution. In 2008, a countrywide survey on Plasmodium falciparum diagnosed in health centres and villages was initiated to develop a detailed P. falcipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…The monitoring of the susceptibility status of Anopheles to insecticides should be performed regularly as this provides essential information for the correct choice of insecticide to be most effective in vector control. Most studies suggest that ITNs can provide a fair degree of protection if properly used [66,63,67,68,69]. Therefore, Cambodia has actively distributed ITNs to many at-risk populations.…”
Section: Distribution Of Malaria Vectors and Behavior Of Anopheles Spmentioning
confidence: 99%
See 2 more Smart Citations
“…The monitoring of the susceptibility status of Anopheles to insecticides should be performed regularly as this provides essential information for the correct choice of insecticide to be most effective in vector control. Most studies suggest that ITNs can provide a fair degree of protection if properly used [66,63,67,68,69]. Therefore, Cambodia has actively distributed ITNs to many at-risk populations.…”
Section: Distribution Of Malaria Vectors and Behavior Of Anopheles Spmentioning
confidence: 99%
“…A field survey for malaria prevalence in southern Laos using molecular-based parasite detection assay showed that mixed species infections were common with all 4 human plas-modia species detected among 23.1% of positive samples [82]. A recent national survey of the malaria distribution revealed that approximately 41% of the country's population is living in areas of no malaria transmission, particularly large areas in the central regions of the country while malaria incidence of more than 1 per 1,000 population is occurring in seven provinces, Saravane, Savannakhet, Sekong, Attapeu, Champasack, Khammouan, Phongsaly, collectively representing 36% of the Lao population [3,69]. Significant reductions have been reported following investments in malaria control, in particular the large-scale introduction of artemi sinin-based combination therapy (ACT) beginning in 2004, ITNs introduced in 2000, and IRS in 2010, in conjunction with socio-economic and environmental changes [3].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The main findings from the use of this map showed that Plasmodium falciparum dominated spatially in the northern and central regions of the country, while large areas did not have any transmission; the areas in which transmission and risk were high were in the southern regions. Additionally, 60% of the population was found to be at risk of contracting malaria (Jorgensen et al, 2010). In China, the central-south counties of Hainan had the highest malaria incidences with 75% of cases recorded during May and October and a positive correlation between cases and climatic factors such as temperature (Xiao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the geographical distribution of malaria in southern and southeastern Asia, a few studies illustrate the spatial or spatiotemporal risk distribution of malaria or its vectors and link the distribution with the current climatic factor values or economic resources. For instance, in Lao People's Democratic Republic (Lao PDR), a detailed P. falciparum risk map was developed and used to identify populations at risk and to guide resource allocation for the ultimate purpose of malarial control (Jorgensen et al, 2010). The main findings from the use of this map showed that Plasmodium falciparum dominated spatially in the northern and central regions of the country, while large areas did not have any transmission; the areas in which transmission and risk were high were in the southern regions.…”
Section: Introductionmentioning
confidence: 99%